PFAPA syndrome: a case report (BIRDEM Medical Journal, 2024)
Periodic fever, aphthous stomatitis, pharyngitis and cervical adenitis (PFAPA) syndrome is a complex autoinflammatory disease characterized by recurrent episodes of fever and systemic inflammatory features. It is usually a disease of children but adult onset has also been reported. The common clinical features are aphthous stomatitis, cervical lymphadenitis, pharyngitis etc with exclusion of upper respiratory tract infection and cyclic neutropenia. The patient remains completely asymptomatic between the episodes of these clinical features with normal growth and development. Here we report a case of 20-year-old male who presented with features suggestive of PFAPA syndrome and well responded with a single dose of high dose prednisolone.BIRDEM Med J 2024; 14(3): 161-165